2019
DOI: 10.3390/tropicalmed4040124
|View full text |Cite
|
Sign up to set email alerts
|

Zero Endemic Cases of Wildlife Rabies (Classical Rabies Virus, RABV) in the European Union by 2020: An Achievable Goal

Abstract: The elimination of rabies transmitted by Classical Rabies Virus (RABV) in the European Union (EU) is now in sight. Scientific advances have made it possible to develop oral vaccination for wildlife by incorporating rabies vaccines in baits for foxes. At the start of the 1980s, aerial distribution of vaccine baits was tested and found to be a promising tool. The EU identified rabies elimination as a priority, and provided considerable financial and technical resources to the infected EU Member States, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 30 publications
2
41
0
6
Order By: Relevance
“…The immunisation was carried out by oral route of application with bait vaccines. Following the recommendation of the European Union, the bait density distributed on the vaccinated site was 20/km 2 (Maki et al, 2017;Robardet et al, 2019). Since that time, the carnivore fauna of southeastern Europe has been changed definitely.…”
Section: Introductionmentioning
confidence: 99%
“…The immunisation was carried out by oral route of application with bait vaccines. Following the recommendation of the European Union, the bait density distributed on the vaccinated site was 20/km 2 (Maki et al, 2017;Robardet et al, 2019). Since that time, the carnivore fauna of southeastern Europe has been changed definitely.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that in areas with low dog accessibility, parenteral vaccination was either ineffective or inefficient, but ORV was able to achieve adequate coverage while remaining a cost-effective public health intervention (42,(45)(46)(47)(48). Although ORV has been used for >40 years in highincome countries to successfully control and eliminate rabies in wildlife (24,27), hesitancy to implement ORV as a component of mass dog vaccination campaigns has resulted in a dearth of evidence to argue for the integration, impact, and cost of these vaccines in the context of dog rabies control.…”
Section: Rationale For the Consideration Of Oral Vaccines For Dog Vacmentioning
confidence: 99%
“…A great paradox exists in the field of global rabies elimination: oral rabies vaccination (ORV) is the main component of elimination of rabies from wildlife populations, which cause only modest human deaths (24)(25)(26)(27), whereas ORV is not used to complement parenteral vaccination for elimination of rabies in dog populations (28), which are responsible for more human deaths than any other single zoonotic pathogen. At present, parenteral vaccination is the only approach used for addressing dog-mediated rabies at-scale, despite frequent publications and field reports of the inadequacies of this approach among important subpopulations of susceptible dogs (Table 1) (39).…”
mentioning
confidence: 99%
“…A gradual decrease in the total number of cases among this species was observed over the years. Since 2017, the overall yearly number of rabies cases has been below 10 and only four EU countries have reported cases: Lithuania, Romania, Poland and Hungary [11]. In addition, Norway reported the detection of rabies cases among Arctic foxes on the islands of Svalbard and Jan Mayen.…”
Section: Rabies In Terrestrial Mammalsmentioning
confidence: 99%
“…Oral rabies vaccination campaigns have been remarkably successful in controlling the infection in red foxes. In the EU/EEA in 2019, only a small number of animal cases occurred, all in eastern EU countries, and achieving elimination of rabies in mammals (no enzootic circulation of the virus and low number of imported cases) has been achieved by 2020 [ 11 ]. Between 2010 and 2019, the highest proportion of animal cases were found in red foxes ( Table 3 ).…”
Section: Animal Rabies Casesmentioning
confidence: 99%